2012
DOI: 10.1152/ajpregu.00276.2012
|View full text |Cite
|
Sign up to set email alerts
|

Insulin reduces excitation in gastric-related neurons of the dorsal motor nucleus of the vagus

Abstract: The dorsal motor nucleus of the vagus (DMV) in the caudal brain stem is composed mainly of preganglionic parasympathetic neurons that control the subdiaphragmatic viscera and thus participates in energy homeostasis regulation. Metabolic pathologies, including diabetes, can disrupt vagal circuitry and lead to gastric dysfunction. Insulin receptors (IRs) are expressed in the DMV, and insulin crosses the blood-brain barrier and is transported into the brain stem. Despite growing evidence that insulin action in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…We recently reported that insulin inhibited the membrane potential directly and suppressed glutamatergic excitatory neurotransmission in DMV neurons in a concentration-related fashion but had no effect on GABA release in the DMV under normal conditions (8). Here, all recordings were made with Cs-based internal recording solutions to block K ϩ conductances and, therefore, prevent direct effects of insulin on the neuronal membrane of the recorded cell, which were previously shown to be K ϩ -dependent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that insulin inhibited the membrane potential directly and suppressed glutamatergic excitatory neurotransmission in DMV neurons in a concentration-related fashion but had no effect on GABA release in the DMV under normal conditions (8). Here, all recordings were made with Cs-based internal recording solutions to block K ϩ conductances and, therefore, prevent direct effects of insulin on the neuronal membrane of the recorded cell, which were previously shown to be K ϩ -dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin action in the brain influences many factors involved in energy homeostasis, including hepatic glucose production (22,42,46,50), food intake (10), and satiety (5). At least some of these actions occur in the DVC, where insulin directly modulates vagal motor neuron activity (8). The brain, in particular, the DVC, is both affected by and contributes to blood glucose dysregulation associated with diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The effect of insulin on the baroreceptor reflex in nucleus tractus solitarii (NTS) is probably mediated by a change in sympathetic nervous activity. 4,5 Furthermore, sympathectomy can prevent the development of fructose-induced hypertension in rats. 6 Recent studies suggest that fructose consumption increases superoxide generation and attenuates baroreflex response.…”
mentioning
confidence: 99%
“…Useful labeling of DMV and NTS neurons occurs after 60 -72 h, a time well before onset of cellular or functional degradation (Card et al 1993;Glatzer et al 2003;Smith et al 2000). This method allows preganglionic DMV motor neurons and synaptically connected, premotor NTS neurons that are specifically related to gastric motor output to be identified and targeted for electrophysiological recording in the in vitro brain stem slice preparation (Blake and Smith 2012;Davis et al 2003;Derbenev et al 2004;Gao et al 2009;Gao and Smith 2010;Glatzer et al 2003Glatzer et al , 2007Glatzer and Smith 2005;Smith et al 2000;Williams et al 2007). Neurons expressing EGFP or mRFP1 were visualized in living tissue under epifluorescence by using fluorescein isothiocyanate (FITC) or tetramethylrhodamine isothiocyanate (TRITC) filter sets.…”
Section: Methodsmentioning
confidence: 99%